2008
DOI: 10.1152/physiolgenomics.90281.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro maturation on gene expression in rhesus monkey oocytes

Abstract: In vitro oocyte maturation (IVM) holds great promise as a tool for enhancing clinical treatment of infertility, enhancing availability of nonhuman primates for development of disease models, and facilitating endangered species preservation. However, IVM outcomes have remained significantly below the success rates obtained with in vivo matured (VVM) oocytes from humans and nonhuman primates. A cDNA array-based analysis is presented, comparing the transcriptomes of VVM oocytes with IVM oocytes. We observe a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 115 publications
2
26
0
Order By: Relevance
“…Recent studies indicated alterations in the transzonal processes between the cumulus cells and oocyte with rhesus monkey IVM (20). We reported recently that the transcriptomes of IVM and VVM metaphase II stage oocytes displayed a very limited degree of difference, with only 59 mRNAs showing significant alterations, most of which were mRNAs that failed to decline in abundance appropriately (38). Here, we examine the transcriptomes of the companion cumulus cells.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies indicated alterations in the transzonal processes between the cumulus cells and oocyte with rhesus monkey IVM (20). We reported recently that the transcriptomes of IVM and VVM metaphase II stage oocytes displayed a very limited degree of difference, with only 59 mRNAs showing significant alterations, most of which were mRNAs that failed to decline in abundance appropriately (38). Here, we examine the transcriptomes of the companion cumulus cells.…”
mentioning
confidence: 96%
“…It is remarkable that the difference between IVM and VVM in the rhesus monkey, yielding such a profound effect on oocyte quality (38,(62)(63)(64)(65)(66), is just that the last 24 h of maturation in response to hormonal stimulation occurs within cumulus-oocyte complexes (COCs) that have been removed from the follicular environment. This indicates that follicular signals during the final 24 h of maturation must normally modulate cumulus cell and/or oocyte phenotype in a manner that confers high oocyte quality.…”
mentioning
confidence: 99%
“…More recently, Lee et al, (2008) reported a small number of transcriptional differences between rhesus monkey oocytes matured in vitro and in vivo. Interestingly, approximately 90% of the identified transcripts were upregulated or overexpressed in IVM oocytes.…”
Section: Modulating Transcriptional Activity In the Oocyte Genomementioning
confidence: 99%
“…24 Finally, overexpression of the MEST gene has been described following in vitro maturation of rhesus monkey oocytes. 25 Aberrant methylation at MEST is associated with certain forms of male infertility. Hypermethylation of MEST has been described in males with oligozoospermia, 26,27 and also idiopathic male infertility.…”
Section: Introductionmentioning
confidence: 99%